Integrated transcriptomics and metabolomics analysis provide insight into anthocyanin biosynthesis for sepal color formation in Heptacodium miconioides - Li, Yueling; Sun, Zhongshuai; Lu, Jieyang; Jin, Zexin; Li, Junmin (Frontiers in Plant Science, 2023)
Heptacodium miconioides Rehd., commonly known as “seven-son flower,” is an ornamental species with a beautiful flower pattern and persistent sepals. Its sepals are of horticultural value, turning bright red and elongating in the autumn; however, the molecular mechanisms that cause sepal color change remain unclear. We analyzed the dynamic changes in anthocyanin composition in the sepal of H. miconioides at four developmental stages (S1-S4). A total of 41 anthocyanins were detected and classified into 7 major anthocyanin aglycones. High levels of the pigments cyanidin-3,5-O-diglucoside, cyanidin-3-O-galactoside, cyanidin-3-O-glucoside, and pelargonidin-3-O-glucoside were responsible for sepal reddening. Transcriptome analysis revealed 15 differentially expressed genes involved in anthocyanin biosynthesis that were detected between 2 developmental stages. Of these, the high expression of HmANS was considered critical structural gene related to anthocyanin biosynthesis pathway in the sepal through co-expression analysis with anthocyanin content. In addition, a transcription factor (TF)-metabolite correlation analysis revealed that three HmMYB, two HmbHLH, two HmWRKY, and two HmNAC TFs exhibited a strong positive role in the regulation of the anthocyanin structural genes (Pearson’s correlation coefficient > 0.90). Luciferase activity assay showed that HmMYB114, HmbHLH130, HmWRKY6, and HmNAC1 could activate the promoters of HmCHS4 and HmDFR1 genes in vitro. These findings increase our understanding of anthocyanin metabolism in the sepal of H. miconioides and provide a guide for studies involving sepal color conversion and regulation.